Essential metrics for assessing the success of physical education at the local government level - Slobodyanyuk B.V.; Myakonkov V.B.; Mustafina D.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to process of determining and validating the essential metrics that enable the evaluation of the success of physical education initiatives at the local government level. Methods and structure of the study. The research employed a combination of methods, including participant observation, expert evaluation, and mathematical statistical analysis. The empirical data encompassed a set of criteria and ten indicators of physical fitness, which are commonly used at the municipal level. A questionnaire was created for experts to assess the importance of these criteria for evaluating the success of physical education initiatives at the municipal level. The criteria were ranked based on their average score (median), the degree of consensus among experts (interquartile range), and the first quartile. Results and conclusions. Assessing the efficacy of physical education necessitates a comprehensive approach that encompasses both quantitative and qualitative metrics. The research underscores the importance of developing initiatives to foster physical culture and sports, which entails organizing informational campaigns to raise public awareness about the significance of physical activity. Hosting sports festivals and other events can greatly contribute to this endeavor. The key metrics are: the number of children and adolescents aged 6-15 who participate in sports programs on a regular basis. The proportion of residents who have achieved the standards set by the All-Russian Physical Culture and Sports Complex «Ready for Work and Defense» (GTO). The percentage of the population actively engaged in physical education and sports compared to the total population. These metrics directly impact the physical activity levels of the population at the municipal level.